Coated substrate and method for producing coated substrate

A coated substrate with a laminated stripe structure and controlled composition addresses the limitations of conventional substrates, offering enhanced stress resistance and thermal stability for diverse applications.

JP2025017992APending Publication Date: 2025-02-06NITERRA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023121351
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Conventional coated substrates lack the necessary functionality and versatility for various applications, and there is a need for improved substrates with enhanced properties such as stress resistance and thermal stability.

Method used

A coated substrate with a thickness of 60 nm to 10 μm, containing 0.1 to 20 atm% carbon, 70 to 100 atm% metal and oxygen elements, and featuring a laminated stripe structure with arranged vacant and non-vacant layers, manufactured using a bath liquid with low moisture and specific metal and halogen elements, and a controlled drying process.

Benefits of technology

The novel coated substrate provides high functionality, stress resistance, and thermal stability, enabling mass production with cost-effectiveness and applicability to diverse fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017992000001_ABST
    Figure 2025017992000001_ABST
Patent Text Reader

Abstract

To provide a novel coated substrate which is applicable to various fields and from which high functionality can be expected.SOLUTION: A coated substrate 1 comprises a substrate 5 coated with a film 3. The film 3 has a thickness of 60 nm or more and 10 μm or less. When the film 3 is measured, the elemental percentage of C (carbon) is 0.1 atm% or more and less than 20 atm%, and the total elemental percentage of metal elements and O (oxygen) is 70 atm% or more. The film 3 contains a plurality of pores 13 that are arranged to form a row in a direction D along a surface S of the substrate 5.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to coated substrates and methods of making coated substrates. [Background technology]

[0002] Patent Documents 1 to 4 disclose coated substrates with metal oxide films. In Patent Documents 1 to 4, a wet film-forming method is adopted. On the other hand, a dry film-forming method (dry process) is sometimes adopted to control the thickness according to the complex shape of the substrate. Considering the performance when applied to various fields, conventional coated substrates are not necessarily sufficient, and the development of new coated substrates has been eagerly desired. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-32521 A [Patent Document 2] JP 2009-147192 A [Patent Document 3] JP 2015-93821 A [Patent Document 4] Japanese Patent Application Publication No. 9-202606 Summary of the Invention [Problem to be solved by the invention]

[0004] The present disclosure has been made in view of the above-mentioned circumstances, and has an object to provide a novel coated substrate that can be applied to various fields and is expected to have high performance. The present disclosure can be realized in the following aspects. [Means for solving the problem]

[0005] [1] A coated substrate in which a substrate is coated with a coating, The thickness of the coating is 60 nm or more and 10 μm or less, When the coating was measured, the element percentage of C (carbon) was 0.1 atm% or more and less than 20 atm%, The total element percentage of metal elements and O (oxygen) is 70 atm% or more, A coated substrate, wherein the coating has a plurality of pores arranged in a row along the surface of the substrate. [2] The coated substrate according to [1], wherein a portion of the substrate where the coating is formed has electrical conductivity. [3] The coated substrate according to [1] or [2], wherein the coating has a striped structure in a cross section of the coating, in which a void-containing layer in which the row of voids is present and a void-free layer in which the row of voids is not present are stacked. [4] The coated substrate according to [3], wherein the void-containing layer is a layer having 5 or more voids per 1000 nm of an imaginary line parallel to the substrate. [5] The coated substrate according to [3], wherein two or more of the non-void layers are present. [6] The thickness of the hole-existing layer is 30 nm or more and 500 nm or less, The coated substrate according to [3], wherein the void-free layer has a thickness of 30 nm or more and 500 nm or less. [7] The coated substrate according to [1] or [2], wherein the metal element is at least one selected from the group consisting of Al (aluminum), Ti (titanium), Zr (zirconium), Mo (molybdenum), W (tungsten), V (vanadium), Fe (iron), Cr (chromium), Co (cobalt), and Mn (manganese). [8] A method for producing a coated substrate using a bath liquid containing an organic solvent, comprising the steps of: The bath liquid has a water content of less than 5% by mass, contains at least one metal element, and contains at least one halogen element; a forming step of forming a coating layer containing the metal element on the negative electrode side of the substrate by applying a voltage while the substrate is immersed in the bath liquid; A drying step of drying the coating layer, A method for producing a coated substrate, in which a set of the forming step and the drying step is repeated to form a coating having a striped structure in which a void layer, in which a plurality of voids are present in a row along the surface of the substrate, and a void-free layer, in which the row of voids is not present, are stacked. [9] The drying step includes: The starting temperature is 5°C or higher and 40°C or lower. The maximum temperature is 100°C or more and 1000°C or less. The method for producing a coated substrate according to [8], wherein the heating rate from the starting temperature to the maximum temperature is 10° C. / min or more and 300° C. / min or less. Effect of the Invention

[0006] According to the present disclosure, a novel coated substrate is provided that is applicable to various fields and can be mass-produced. The coating also contains a number of pores arranged in rows along the surface of the substrate, a structure that is expected to contribute to stress relaxation. [Brief description of the drawings]

[0007] [Figure 1] 1 is a cross-sectional image of an example of a coated substrate observed by FIB-SEM. [Diagram 2] FIG. 1 is a schematic diagram of a cross section of an example of a coated substrate. [Diagram 3] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present disclosure will be described in detail below. In this specification, when a numerical range is described using "-", the lower limit and the upper limit are included unless otherwise specified. For example, the description "10-20" includes both the lower limit "10" and the upper limit "20". In other words, "10-20" has the same meaning as "10 or more and 20 or less". In this specification, the upper limit and the lower limit of each numerical range can be arbitrarily combined.

[0009] 1.Coated substrate 1 The coated substrate 1 is formed by coating a substrate 5 with a coating 3. The thickness of the coating 3 is 60 nm or more and 10 μm or less. When the coating 3 was measured, the element percentage of C (carbon) was 0.1 atm% or more and less than 20 atm%, and the total element percentage of metal elements and O (oxygen) was 70 atm% or more. In the coating 3, a plurality of pores 13 are present that are aligned in a row in a direction along the surface of the substrate 5.

[0010] (1) Base material 5 The substrate 5 is not particularly limited. In order to enhance the adhesion of the coating 3 to the substrate 5, at least the portion (region) of the substrate 5 covered by the coating 3 is preferably made of a material that has electrical conductivity and can become a negative electrode 7 (cathode). By making the portion of the substrate 5 covered by the coating 3 conductive and becoming a negative electrode 7 (cathode), the coating 3 can be easily formed on this portion by applying a voltage. The surface of the substrate 5 may be made of a material that is conductive and can be the negative electrode 7. The entire substrate 5 may be made of a material that can be the negative electrode 7. For example, an iron-based alloy or carbon is preferably used as the material that can be the negative electrode 7. Suitable examples of the iron-based alloy include one or more selected from Fe-Ni-Cr-based alloys (austenitic stainless steel), Fe-Cr-based alloys (ferritic stainless steel), Fe-Ni-based alloys (permalloy), Fe-Si-based alloys (iron silicon), Fe-Si-Al-based alloys (sendust), Fe-Ni-Mo (supermalloy), Fe-Co-based alloys (permendur), Fe-Ni-Co-based alloys (kovar), and Fe-CB-based alloys (amorphous).

[0011] (2) Coating 3 (2.1) Thickness The thickness of the coating 3 is 60 nm or more, preferably 200 nm or more, and more preferably 300 nm or more, from the viewpoint of exerting a function according to the material of the coating 3. On the other hand, from the viewpoint of enduring the stress generated in the coating 3 and ensuring adhesion to the substrate 5, the thickness is 10 μm or less, preferably 1000 nm or less, and more preferably 800 nm or less. From these viewpoints, the thickness of the coating 3 is 60 nm or more and 10 μm or less, preferably 200 nm or more and 1000 nm or less, and more preferably 300 nm or more and 800 nm or less. In addition, when the thickness of the coating 3 is not constant, the thickness requirement is satisfied as long as the thickness of at least a part of the coating 3 is within the above-mentioned range. The thickness of the coating 3 can be obtained by observation with a FIB-SEM (dual beam scanning electron microscope).

[0012] (2.2) Elemental percentage of C (carbon) The element percentage of C (carbon) when the coating 3 is measured by X-ray photoelectron spectroscopy (XPS method) is 0.1 atm% or more, preferably 0.5 atm% or more, and more preferably 1 atm% or more, from the viewpoint of suppressing crystal grain growth in the coating 3 and stabilizing the properties of the coating 3. On the other hand, from the viewpoint of allowing the coating 3 to fully function as an inorganic coating, it is less than 20 atm%, preferably 15 atm% or less, and more preferably 10 atm% or less. From these viewpoints, the element percentage of C (carbon) is 0.1 atm% or more and less than 20 atm%, preferably 0.5 atm% or more and 15 atm% or less, and more preferably 1 atm% or more and 10 atm% or less. Note that when the composition of the coating 3 is not constant, the requirement for the element percentage of C (carbon) is satisfied as long as the composition of at least a part of the coating 3 is within the above-mentioned range. Composition analysis by X-ray photoelectron spectroscopy can be performed using an X-ray photoelectron spectrometer. The measurement conditions are as follows: the X-ray source is aluminum metal K-alpha ray, the beam diameter is 100 μm, and the X-ray incidence angle to the surface to be analyzed is 45°, and the cross section is scanned.

[0013] (2.3) Total element percentage of metal elements and O (oxygen) The total element percentage of metal elements and O (oxygen) when the coating 3 is measured by X-ray photoelectron spectroscopy (XPS method) is 70 atm% or more, preferably 80 atm% or more, and more preferably 90 atm% or more, from the viewpoint of allowing the coating 3 to function sufficiently as an inorganic coating. The upper limit of the total element percentage of metal elements and O (oxygen) is the value obtained by subtracting the element percentage (atm%) of C (carbon) from 100 atm%. When the composition of the coating 3 is not constant, the requirement for the total element percentage of metal elements and O (oxygen) is satisfied as long as the composition of at least a part of the coating 3 is within the above-mentioned range.

[0014] (2.4) Structure of Coating 3 (2.4.1) Row of 13 holes The coating 3 has a plurality of voids 13 arranged in a row in a direction D along the surface S of the substrate 5 (see FIGS. 1 and 2). The row of voids 13 in the coating 3 is expected to function as a stress relaxation layer and / or a thermal relaxation layer. When a cross section of the film 3 cut in the film thickness direction is observed with a FIB-SEM (dual beam scanning electron microscope), the rows of pores 13 in the film 3 can be confirmed. The average diameter of the pores 13 is not particularly limited. From the viewpoint of allowing the row of pores 13 to exert the function of stress relaxation and / or thermal relaxation, the average diameter of the pores 13 is preferably 1 nm or more and 30 nm or less, more preferably 5 nm or more and 30 nm or less, and even more preferably 10 nm or more and 30 nm or less. The average diameter of the pores 13 can be calculated as follows. A cross section of the coating 3 cut in the film thickness direction is observed by FIB-SEM, and the area-equivalent circle diameter of each of 10 pores 13 is calculated from the area of ​​each pore 13, and these area-equivalent circle diameters are averaged to calculate the average.

[0015] (2.4.2) Striped structure From the viewpoint of improving resistance to stress, it is preferable that the coating 3 has a striped structure (horizontal striped structure) in the above cross section of the coating 3, in which a void-present layer La in which a row of voids 13 exists and a void-free layer Lb (dense layer) in which no row of voids 13 exists are stacked (see Figures 1 and 2).

[0016] (2.4.3) Number of vacancies 13 in the vacancy-existing layer La The number of voids 13 in the void-containing layer La is not particularly limited, but from the viewpoint of effectively exerting the function as a stress relaxation layer and / or a heat insulating layer, the void-containing layer La is preferably a layer having 5 or more voids 13 per 1000 nm of a virtual line L parallel to the substrate 5 (see FIG. 2). This requirement is not determined for the entire void-containing layer La, but for a portion of it. In other words, if even a portion of the void-containing layer La satisfies this requirement, it is considered to satisfy this requirement. In addition, if there are multiple void-containing layers La, it is considered to satisfy this requirement if at least one of the void-containing layers La satisfies this requirement. The number of holes 13 per 1000 nm of the imaginary line L in the hole-existing layer La is more preferably 5 to 100, and further preferably 10 to 50.

[0017] (2.4.4) Hole-free layer Lb The number of the hole-free layers Lb is not particularly limited. From the viewpoint of ensuring the strength of the coating 3, it is preferable that two or more void-free layers Lb are present. From the viewpoint of ensuring adhesion between the coating 3 and the substrate 5, the layer in contact with the substrate 5 is preferably the void-free layer Lb. In order to ensure the surface physical properties of the coating 3, such as hardness and chemical resistance, the outermost layer of the coating 3 is preferably a void-free layer Lb.

[0018] (2.4.5) Thickness of vacancy layer La and vacancy-free layer Lb The thicknesses of the void-containing layer La and the void-free layer Lb are not particularly limited. From the viewpoint of ensuring the strength of the coating 3, the thickness of the pore-containing layer La is preferably 30 nm or more and 500 nm or less, more preferably 60 nm or more and 200 nm or less, and even more preferably 80 nm or more and 150 nm or less. From the viewpoint of ensuring the strength of the coating 3, the thickness of the void-free layer Lb is preferably 30 nm or more and 500 nm or less, more preferably 60 nm or more and 200 nm or less, and even more preferably 80 nm or more and 150 nm or less.

[0019] (2.5) Amorphous The coating 3 is preferably amorphous. The amorphous nature of the coating 3 can be confirmed by using a TEM electron diffraction method. If the coating 3 is amorphous, the falling off of crystal grains is suppressed, and the coating 3 is expected to exhibit unique functions such as smoothing of the outermost surface due to uniform film growth.

[0020] (2.6) Halogen elements When the coating 3 is measured by X-ray photoelectron spectroscopy, the percentage of the halogen element is preferably 0.1 atm% or more, more preferably 0.3 atm% or more, and even more preferably 0.5 atm% or more. The upper limit of the percentage of the halogen element is 3 atm% or less. The halogen element is preferably at least one selected from the group consisting of I (iodine), Cl (chlorine), and Br (bromine). It is believed that the trace amounts of halogen elements contained in coating 3 cause the oxide coating present on the surface of substrate 5 to be removed by the action of the halogen elements, resulting in a structure in which coating 3 and substrate 5 are in direct contact with each other, thereby ensuring adhesion between substrate 5 and coating 3.

[0021] (2.7) Metal elements The metal element is not particularly limited. From the viewpoint of easily forming a coating 3 having improved strength by a manufacturing method described later, the metal element is preferably at least one selected from the group consisting of Al (aluminum), Ti (titanium), Zr (zirconium), Mo (molybdenum), W (tungsten), V (vanadium), Fe (iron), Cr (chromium), Co (cobalt), and Mn (manganese).

[0022] 2. Method for producing coated substrate 1 The method for producing the coated substrate 1 of the present disclosure is not particularly limited. A preferred manufacturing method will be described below. A preferred manufacturing method is a method for manufacturing the coated substrate 1 using a bath liquid 2 using an organic solvent as a solvent. The bath liquid 2 has a water content of less than 5% by mass, contains at least one metal element, and contains at least one halogen element. This manufacturing method has a forming step of forming a coating layer 3 containing a metal element on the substrate 5 on the negative electrode 7 side (cathode side) by applying a voltage while the substrate 5 is immersed in the bath liquid. This manufacturing method also has a drying step of drying the coating layer 3. In this manufacturing method, a set of the forming step and the drying step is repeated to form a coating 3 having a striped structure in which a vacancy-containing layer La in which a plurality of vacancies 13 are present aligned in a direction D along the surface S of the substrate 5 and a vacancy-free layer Lb in which no row of vacancies 13 is present are laminated. In the manufacturing method of the present disclosure, by electrodeposition on the negative electrode 7 side, oxidation of the substrate 5 can be suppressed more effectively than by electrodeposition on the positive electrode 6 side (anode side).

[0023] (1) Bath liquid 2 The bath liquid 2 contains an organic solvent as a solvent. (1.1) Moisture content From the viewpoint of ensuring the homogeneity of the coating 3 and suppressing oxidation of the substrate 5, the water content of the bath liquid 2 is set to less than 5 mass%. The water content is preferably less than 3 mass%, and more preferably less than 0.1 mass%. The water content may be 0 mass%. The water content of the bath liquid 2 can be determined by GC-MS analysis.

[0024] (1.2) Metallic elements The bath liquid 2 contains at least one metal element. The metal element is not particularly limited. From the viewpoint of making the coating 3 function as a good protective film for the substrate 5, the metal element is preferably at least one selected from the group consisting of Al (aluminum), Ti (titanium), Zr (zirconium), Mo (molybdenum), W (tungsten), V (vanadium), Fe (iron), Cr (chromium), Co (cobalt) and Mn (manganese). In the manufacturing method of the present disclosure, an oxide film, which is the coating 3, is formed depending on the metal element in the bath liquid 2. The metal element contained in the bath liquid 2 may be supplied to the bath liquid 2 by dissolution from the positive electrode 6 (anode). When the metal element dissolves from the positive electrode 6 into the bath liquid 2, it becomes easy to control the film formation rate, and it becomes possible to continuously and stably form films on a plurality of substrates 5. When the metal element is supplied to the bath liquid 2 by dissolution from the positive electrode 6, it is preferable that the positive electrode 6 be at least one type of electrode selected from an Al electrode, a Ti electrode, and a Mo electrode. The metal elements in the bath liquid 2 may be supplied from metal alkoxides and / or inorganic metal compounds. When the metal elements are supplied by dissolving metal alkoxides and / or inorganic metal compounds, it is possible to deal with elements that are difficult to supply by dissolving the positive electrode 6 (anode). In this case, it is also possible to form a film in which a composition ratio is controlled by combining a plurality of metal elements. Examples of metal alkoxides include aluminum alkoxides, titanium alkoxides, and molybdenum alkoxides. Examples of aluminum alkoxides include aluminum trialkoxides. Examples of aluminum trialkoxides include aluminum tripropoxides (e.g., aluminum triisopropoxide, aluminum tri-n-propoxide), aluminum triethoxide, aluminum tributoxides (e.g., aluminum trisec-butoxide, aluminum tri-n-butoxide), and the like. Examples of titanium alkoxides include titanium trialkoxides and titanium tetraalkoxides, and preferably titanium tetraalkoxides. Examples of titanium tetraalkoxides include titanium tetrapropoxides (e.g., titanium tetraisopropoxide, titanium tetra n-propoxide, etc.), titanium tetramethoxide, titanium tetraethoxide, titanium tetrabutoxides (e.g., titanium tetraisobutoxide, titanium tetra n-butoxide, etc.), titanium tetrapentoxide, titanium tetrahexoxide, titanium tetra(2-ethylhexoxide), etc. Examples of the inorganic metal compound include aluminum chloride, aluminum bromide, aluminum iodide, and titanium iodide. When the metal element in the bath liquid 2 is supplied from a metal alkoxide and / or an inorganic metal compound, the concentration of the metal element in the bath liquid 2 is not particularly limited. In this case, from the viewpoint of forming a good coating 3, the concentration of the metal element in the bath liquid 2 is preferably 1 ppm or more and 100 ppm or less, more preferably 3 ppm or more and 10 ppm or less, and even more preferably 4 ppm or more and 6 ppm or less. Here, "ppm" stands for "parts per million" and "mg / L". In addition, when the bath liquid 2 contains multiple metal elements, the concentration of the metal element means the total concentration of the multiple metal elements. The concentration of the metal element in the bath liquid 2 can be measured by ICP-MS analysis.

[0025] (1.3) Halogen elements The bath liquid 2 contains at least one type of halogen element. By containing a halogen element in the bath liquid 2, the film formation is carried out at a practical speed, and the film 3 is likely to be homogeneous. The halogen element is not particularly limited. From the viewpoint of rapidly progressing the organic electrochemical reaction and allowing the film 3 to function as a good protective film for the substrate 5, the halogen element is preferably at least one selected from the group consisting of Cl (chlorine), Br (bromine), and I (iodine). The concentration of the halogen element in the bath liquid 2 is not particularly limited. From the viewpoint of appropriately suppressing the reaction rate, being advantageous in controlling the uniformity and thickness of the coating 3, and suppressing peeling of the coating 3, the concentration of the halogen element is preferably 1 ppm or more and 20,000 ppm or less, more preferably 5 ppm or more and 2,000 ppm or less, and even more preferably 10 ppm or more and 100 ppm or less. Note that "ppm" means "parts per million" and "mg / L". The concentration of the halogen element in the bath liquid 2 can be determined from the amount of halogen element added when the bath is made, or by ICP-MS analysis of the bath liquid.

[0026] (1.4) Organic solvents By using an organic solvent as the solvent for the bath liquid 2, gas generation during film formation and oxidation of the substrate 5 itself are suppressed. From the viewpoint of favorable formation of the film 3, it is preferable that the solvent contains at least one selected from the group consisting of ketones and nitriles. It is presumed that the inclusion of a ketone or nitrile in the solvent causes a condensation reaction to occur on the electrode surface (cathode surface), making electrodeposition possible. It is also presumed that the inclusion of a ketone in the solvent causes keto-enol tautomerism in the presence of a halogen, improving the reactivity of the bath liquid 2.

[0027] (1.4.1) Ketones The ketone is not particularly limited as long as it is an organic solvent having a carbonyl group (-C(=O)-) other than an ester bond. Examples of ketones include acetone, methyl ethyl ketone (MEK), 1-hexanone, 2-hexanone, 4-heptanone, 2-heptanone (methyl amyl ketone), 1-octanone, 2-octanone, 1-nonanone, 2-nonanone, diisobutyl ketone, methyl isobutyl ketone, acetylacetone, acetonylacetone, phenylacetone, acetophenone, methyl naphthyl ketone, cyclohexanone (CHN), methylcyclohexanone, etc. Among these, from the viewpoint of particularly favorable formation of the coating 3, acetone and methyl ethyl ketone are preferred as the ketone.

[0028] (1.4.2) Nitriles The nitrile is an organic solvent containing a nitrile group (-CN) in the structure. Examples of the nitrile include acetonitrile, propionitrile, valeronitrile, butyronitrile, etc. Among these, acetonitrile is preferable as the nitrile from the viewpoint of forming the coating 3 particularly well.

[0029] (2) Base material 5 For the "substrate 5", the explanation in the "(1) Substrate 5" section in "1. Coated substrate 1" above applies as is.

[0030] (3) Forming the coating layer (voltage application) In the present disclosure, a coating layer is formed on the negative electrode side of the substrate 5 by applying a voltage while the substrate 5 is immersed in the bath liquid. Specifically, the positive electrode 6 and the negative electrode 7 (substrate 5) are immersed in the bath liquid 2, and a potential gradient is generated between the two electrodes. Any known conductive substrate can be used as the positive electrode 6. When the metal element in the bath liquid 2 is supplied by dissolution from the positive electrode 6, the positive electrode 6 is preferably at least one electrode selected from an Al electrode, a Ti electrode, and a Mo electrode. The shape, thickness, size, etc. of the positive electrode 6 are not particularly limited. The positive electrode 6 may be, for example, in the form of a foil, a plate, a foam, a nonwoven fabric, a mesh, a felt, or an expanded form. The positive electrode 6 and the negative electrode 7 are preferably disposed opposite each other. The positive electrode 6 and the negative electrode 7 are connected to a DC power supply, and a potential gradient can be generated between the positive electrode 6 and the negative electrode by the DC power supply. In order to generate a potential gradient between the positive electrode 6 and the negative electrode 7, the positive electrode 6 and the negative electrode 7 are immersed in the bath liquid 2 and a voltage (e.g., a constant voltage) is applied to both electrodes by a power source connected to the positive electrode 6 and the negative electrode 7. From the viewpoint of forming a film at a practical speed, the potential gradient generated between the two electrodes is preferably 10 V or more and 1000 V or less, more preferably 20 V or more and 500 V or less, and even more preferably 40 V or more and 100 V or less, in the case of a constant voltage. The application time of the voltage is not particularly limited, and is, for example, preferably from 10 seconds to 300 seconds, more preferably from 20 seconds to 240 seconds, and further preferably from 30 seconds to 180 seconds. The voltage does not have to be a constant voltage, and may be variable in magnitude.

[0031] (4) Drying process to dry the coating layer The drying temperature is not particularly limited. From the viewpoint of accelerating the hydrolysis reaction and reliably forming a row of pores 13 in the coating 3, it is preferable that the drying temperature be in the range of 5° C. to 40° C. at the start, 100° C. to 1000° C. at the maximum temperature, and the heating rate from the start temperature to the maximum temperature be 10° C. / min to 300° C. / min. The holding time at the maximum temperature is not particularly limited. This holding time is, for example, 1 minute to 1 hour. It is more preferable that the starting temperature is 5°C or higher and 50°C or lower, the maximum temperature is 200°C or higher and 700°C or lower, and the heating rate from the starting temperature to the maximum temperature is 10°C / min or higher and 300°C / min or lower. It is more preferable that the starting temperature is 15°C or more and 25°C or less, the maximum temperature is 300°C or more and 600°C or less, and the heating rate from the starting temperature to the maximum temperature is 20°C / min or more and 200°C / min or less. By setting the maximum temperature to such a high level, shrinkage of the entire film after lamination is suppressed, and the coating 3 can be made strong against stress. Moreover, by using such a high temperature rise rate, the volatile components contained within the film are rapidly gasified, making it easier to form rows of pores 13.

[0032] (5) Repeating the set of forming process and drying process By repeating a set of the forming step and the drying step, a coating 3 having a striped structure in which void-containing layers La and void-free layers Lb in which no rows of voids 13 exist are laminated is formed.

[0033] 3. Effects of the coated substrate 1 of this embodiment According to the present embodiment, a novel coated substrate 1 is provided that is applicable to various fields and is expected to provide high functionality. According to the present embodiment, it is possible to provide a coated substrate 1 having a coating 3 that can withstand higher stress than conventionally. Moreover, according to the present embodiment, the coating 3 has high conformability to the substrate 5. Moreover, according to the present embodiment, the difference in thermal expansion between the coating 3 and the substrate 5 is small. Moreover, according to the present embodiment, it is possible to make the coating 3 thicker than conventionally. The coated substrate 1 of this embodiment can be mass-produced by employing a simple process. The coated substrate 1 of the present embodiment is advantageous in terms of cost because it can be formed without using expensive raw materials or using only small amounts of expensive raw materials. The film formation mechanism in this embodiment is assumed to be as follows. It is assumed that a condensation reaction occurs at the cathode while incorporating metal elements in the solvent, followed by an oxide film formation process in which condensation and hydrolysis occur on the surface of the substrate 5 due to the heat of vaporization during drying. However, this film formation mechanism is merely assumed, and the present disclosure is not bound by this film formation mechanism. EXAMPLES

[0034] The present disclosure will be explained more specifically with reference to examples. In the following description, the measurement conditions for XPS (X-ray photoelectron spectroscopy) are as follows. [Measurement conditions] X-ray beam diameter: 100μmΦ Signal capture angle: 45.0° Pass energy: 140 eV Ar etching for 30 seconds (etching rate: 10 nm / min in SiO2 equivalent)

[0035] 1. Example (1) Example 1 (solvent: acetone, positive electrode 6: aluminum) A film forming apparatus 11 shown in FIG. 3 was used. An aluminum wire was used as the positive electrode 6. A stainless steel plate was used as the negative electrode 7. The negative electrode 7 was a substrate 5 on whose surface a film 3 was formed. Acetone was used as the solvent for the bath liquid 2. 50 ppm of iodine was dissolved in the bath liquid 2 as a halogen. With the positive electrode 6 and the negative electrode 7 immersed in the bath liquid 2, 80 V was applied between the positive electrode 6 and the negative electrode 7 for 1 minute to form a coating layer (forming step). After that, the coated substrate was placed in a dryer at 300°C for 5 minutes and dried by heating in air (drying step). The heating rate until the coated substrate reached 300°C was 50°C / min. By repeating the formation step and drying step 10 times, a film 3 of 564 nm was formed on the surface of the substrate 5. The film thickness of the film 3 was measured by observing the cross section of the negative electrode 7 with a FIB-SEM (field emission scanning electron microscope). Analysis by XPS after Ar etching for 30 seconds revealed that the film 3 was aluminum oxide. Furthermore, the element percentage of carbon element in the coating 3 was 6 atm %, and the total element percentage of aluminum element and oxygen element was 90 atm %. The element percentage of iodine in this film 3 was 0.1 atm %. Furthermore, no diffraction pattern was observed in a cross-sectional TEM electron diffraction analysis of the coating 3 cut in the thickness direction, confirming that the coating 3 was amorphous. A cross section of the coating 3 cut in the thickness direction was observed with a FIB-SEM (dual beam scanning electron microscope). A striped structure in which a plurality of void-containing layers La and a plurality of void-free layers Lb were stacked was confirmed in the coating 3. The thickness of the void-containing layers La was 50 nm or more and 150 nm or less. The thickness of the void-free layers Lb was 50 nm or more and 200 nm or less. In the hole-existing layer La, the number of holes 13 per 1000 nm of an imaginary line L in the direction parallel to the substrate 5 was 14. Furthermore, the layer of the coating 3 that was in contact with the substrate 5 was a void-free layer Lb. The outermost layer of the coating 3 was a void-free layer Lb.

[0036] (2) Example 2 (solvent: acetone, positive electrode 6: aluminum) A film forming apparatus 11 shown in FIG. 3 was used. An aluminum wire was used as the positive electrode 6. An Fe-Ni-Co alloy (Kovar) was used as the negative electrode 7. The negative electrode 7 was a substrate 5 on whose surface a film 3 was formed. Acetone was used as the solvent for the bath liquid 2. 50 ppm of iodine was dissolved in the bath liquid 2 as a halogen. With the positive electrode 6 and the negative electrode 7 immersed in the bath liquid 2, 80 V was applied between the positive electrode 6 and the negative electrode 7 for 1 minute to form a coating layer (forming step). After that, the coated substrate was placed in a dryer at 300°C for 5 minutes and dried by heating in air (drying step). The heating rate until the coated substrate reached 300°C was 50°C / min. By repeating the formation step and drying step nine times, a 500 nm film 3 was formed on the surface of the substrate 5. The thickness of the film 3 was measured by observing the cross section of the negative electrode 7 with a FIB-SEM (field emission scanning electron microscope). Analysis with XPS after Ar etching for 30 seconds revealed that the film 3 was aluminum oxide. Furthermore, the element percentage of carbon element in the coating 3 was 6 atm %, and the total element percentage of aluminum element and oxygen element was 90 atm %. The element percentage of iodine in this film 3 was 0.1 atm %. Furthermore, no diffraction pattern was observed in a cross-sectional TEM electron diffraction analysis of the coating 3 cut in the thickness direction, confirming that the coating 3 was amorphous. A cross section of the coating 3 cut in the thickness direction was observed with a FIB-SEM (dual beam scanning electron microscope). A striped structure in which a plurality of void-containing layers La and a plurality of void-free layers Lb were stacked was confirmed in the coating 3. The thickness of the void-containing layers La was 50 nm or more and 150 nm or less. The thickness of the void-free layers Lb was 50 nm or more and 200 nm or less. In the hole-existing layer La, the number of holes 13 per 1000 nm of an imaginary line L in the direction parallel to the substrate 5 was 12. Furthermore, the layer of the coating 3 that was in contact with the substrate 5 was a void-free layer Lb. The outermost layer of the coating 3 was a void-free layer Lb.

[0037] (3) Example 3 (solvent: acetone, positive electrode 6: aluminum) A film forming apparatus 11 shown in FIG. 3 was used. An aluminum wire was used as the positive electrode 6. Carbon was used as the negative electrode 7. The negative electrode 7 was a substrate 5 on whose surface a film 3 was formed. Acetone was used as the solvent for the bath liquid 2. 50 ppm of iodine was dissolved in the bath liquid 2 as a halogen. With the positive electrode 6 and the negative electrode 7 immersed in the bath liquid 2, 80 V was applied between the positive electrode 6 and the negative electrode 7 for 1 minute to form a coating layer (forming step). After that, the coated substrate was placed in a dryer at 300°C for 5 minutes and dried by heating in air (drying step). The heating rate until the coated substrate reached 300°C was 50°C / min. By repeating the formation step and drying step 10 times, a film 3 of 940 nm was formed on the surface of the substrate 5. The film thickness of the film 3 was measured by observing the cross section of the negative electrode 7 with a FIB-SEM (field emission scanning electron microscope). Analysis by XPS after Ar etching for 30 seconds revealed that the film 3 was aluminum oxide. Furthermore, the element percentage of carbon element in the coating 3 was 8 atm %, and the total element percentage of aluminum element and oxygen element was 90 atm %. The element percentage of iodine in this film 3 was 0.1 atm %. Furthermore, no crystal grains were observed in a cross-sectional TEM image of the coating 3 cut in the thickness direction, confirming that the coating 3 was amorphous. A cross section of the coating 3 cut in the thickness direction was observed with a FIB-SEM (dual beam scanning electron microscope). A striped structure in which a plurality of void-containing layers La and a plurality of void-free layers Lb were stacked was confirmed in the coating 3. The thickness of the hole-containing layer La was 50 nm or more and 150 nm or less, and the thickness of the hole-free layer Lb was 50 nm or more and 200 nm or less. In the hole-existing layer La, the number of holes 13 per 1000 nm of an imaginary line L in the direction parallel to the substrate 5 was 12. Furthermore, the layer of the coating 3 that was in contact with the substrate 5 was a void-free layer Lb. The outermost layer of the coating 3 was a void-free layer Lb.

[0038] 2. Effects of the embodiment According to this embodiment, a novel coated substrate 1 is provided which is applicable to various fields and is expected to provide high functionality.

[0039] The present invention is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present invention.

[0040] (Additional Note) This specification includes the following inventions: [1] A coated substrate comprising a substrate coated with a coating film, The thickness of the coating is 60 nm or more and 10 μm or less, When the coating was measured, the element percentage of C (carbon) was 0.1 atm% or more and less than 20 atm%, The total element percentage of metal elements and O (oxygen) is 70 atm% or more, A coated substrate, wherein the coating has a plurality of pores arranged in a row in a direction along the surface of the substrate. [2] The coated substrate according to [1], wherein a portion of the substrate where the coating is formed has electrical conductivity. [3] The coated substrate according to [1] or [2], wherein the coating has a striped structure in a cross section of the coating, in which a void-containing layer in which the row of voids is present and a void-free layer in which the row of voids is not present are stacked. [4] The coated substrate according to [3], wherein the void-containing layer is a layer having 5 or more voids per 1000 nm of an imaginary line parallel to the substrate. [5] The coated substrate according to [2] or [3], wherein two or more of the non-void layers are present. [6] The thickness of the hole-existing layer is 30 nm or more and 500 nm or less, The coated substrate according to any one of [3] to [5], wherein the void-free layer has a thickness of 30 nm or more and 500 nm or less. [7] The coated substrate according to any one of [1] to [6], wherein the metal element is at least one selected from the group consisting of Al (aluminum), Ti (titanium), Zr (zirconium), Mo (molybdenum), W (tungsten), V (vanadium), Fe (iron), Cr (chromium), Co (cobalt), and Mn (manganese). [8] A method for producing a coated substrate using a bath liquid containing an organic solvent, comprising the steps of: The bath liquid has a water content of less than 5% by mass, contains at least one metal element, and contains at least one halogen element; a forming step of forming a coating layer containing the metal element on the negative electrode side of the substrate by applying a voltage while the substrate is immersed in the bath liquid; A drying step of drying the coating layer, A method for producing a coated substrate, in which a set of the forming step and the drying step is repeated to form a coating having a striped structure in which a void layer, in which a plurality of voids are present in a row along the surface of the substrate, and a void-free layer, in which the row of voids is not present, are stacked. [9] The drying step includes: The starting temperature is 5°C or higher and 40°C or lower. The maximum temperature is 100°C or more and 1000°C or less. The method for producing a coated substrate according to [8], wherein the heating rate from the starting temperature to the maximum temperature is 10° C. / min or more and 300° C. / min or less. [Explanation of symbols]

[0041] 1 ...Coated substrate 2…Bath liquid 3. Coating 5...Base material 6...Positive electrode 7...Negative electrode 11...Film deposition equipment 13...Vacancy

Claims

1. A coated substrate in which a substrate is coated with a coating, The thickness of the coating is 60 nm or more and 10 μm or less, When the coating was measured, the element percentage of C (carbon) was 0.1 atm % or more and less than 20 atm %, The total element percentage of metal elements and O (oxygen) is 70 atm % or more, A coated substrate, wherein the coating has a plurality of pores arranged in a row along the surface of the substrate.

2. The coated substrate according to claim 1 , wherein the portion of the substrate on which the coating is formed is electrically conductive.

3. 3. The coated substrate according to claim 1 or 2, wherein the coating has a striped structure in a cross section of the coating, in which a void-containing layer in which the row of voids is present and a void-free layer in which the row of voids is not present are stacked.

4. The coated substrate according to claim 3 , wherein the void-containing layer is a layer in which 5 or more voids are present per 1000 nm of an imaginary line in a direction parallel to the substrate.

5. The coated substrate of claim 3 wherein there is more than one said nonvoid layer.

6. The thickness of the hole-existing layer is 30 nm or more and 500 nm or less, The coated substrate according to claim 3 , wherein the non-void layer has a thickness of 30 nm or more and 500 nm or less.

7. 3. The coated substrate according to claim 1, wherein the metal element is at least one selected from the group consisting of Al (aluminum), Ti (titanium), Zr (zirconium), Mo (molybdenum), W (tungsten), V (vanadium), Fe (iron), Cr (chromium), Co (cobalt), and Mn (manganese).

8. A method for producing a coated substrate using a bath liquid containing an organic solvent, comprising the steps of: The bath liquid has a water content of less than 5 mass %, contains at least one metal element, and contains at least one halogen element; a forming step of forming a coating layer containing the metal element on the negative electrode side of the substrate by applying a voltage while the substrate is immersed in the bath liquid; A drying step of drying the coating layer, A method for producing a coated substrate, in which a set of the forming step and the drying step is repeated to form a coating having a striped structure in which a void layer, in which a plurality of voids are present in a row along the surface of the substrate, and a void-free layer, in which the row of voids is not present, are stacked.

9. The drying step includes: The starting temperature is 5°C or more and 40°C or less, The maximum temperature is 100°C or more and 1000°C or less, The method for producing a coated substrate according to claim 8, wherein a temperature rise rate from the starting temperature to the maximum temperature is 10° C. / min or more and 300° C. / min or less.

Citation Information

Patent Citations

  • Multilayer oxide thin film element and its production

    JP1997202606A

  • Crystalline inorganic film and method of manufacturing the same, and semiconductor device

    JP2009147192A

  • CSD solution, and CIS-based film forming method using the solution

    JP2011032521A

  • Method of producing titanium oxide film, and titanium oxide film

    JP2015093821A